Persepsi Guru Terhadap Perubahan Kurikulum K13 Ke Kurikulum Merdeka Di SD Negeri 1 Alue Bilie Kecamatan Darul Makmur Kabupaten Nagan Raya - Siti Mardiya; M. Yamin; Intan Safiah (Universitas Syiah Kuala, 2023)
The purpose of this research is to describe teachers' perceptions of changes from the K13 curriculum to an independent curriculum at SD Negeri 1 Alue Bilie, Darul Makmur District, Nagan Raya Regency. The approach taken is qualitative with the type of research that is descriptive. The data collection technique was taken by interviewing the school principal, one of the grade 1 and grade 4 teachers at SD Negeri 1 Alue Bilie. There are data analysis techniques namely data collection, data reduction, data presentation, and conclusion drawing. From the research it was found that teachers' perceptions of the changes in the 2013 curriculum to the independent curriculum at SD Negeri 1 Alue Bilie were very diverse. Most of the teachers perceive that the change from the 2013 curriculum to the independent curriculum is very good and facilitates the achievement of learning objectives. However, no matter how good the concept of curriculum change is, if the teacher is not adaptive and unprepared, it will be difficult to implement it. So as a teacher must be able to implement the curriculum in the education unit properly so that educational goals can be achieved properly.